2018
DOI: 10.1159/000484450
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Dimensions of General Intelligence: An Integrated Differential-Developmental Theory

Abstract: We present a theory of mental architecture and development focusing on general intelligence (g). The theory integrates psychometric and developmental theories of intelligence into an overarching framework. The paper first focuses on the composition of g. It is shown that g involves attention control, flexibility, working memory, cognizance of mental processes, and inference. We then present a model of intellectual development involving four cycles - episodic, realistic representation-based, rule-based, and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 87 publications
3
56
0
4
Order By: Relevance
“…Integrating over different traditions of research, Demetriou and colleagues suggested that cognitive development occurs in four cycles, with two phases in each (Demetriou et al, ; Demetriou & Spanoudis, , ). Moving across cycles is associated with the emergence of new forms of representation; changes within cycles are associated with increasing awareness of them, skill in using them, and in their alignment and interlinking.…”
Section: Development Of Cognizance Executive Control and Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating over different traditions of research, Demetriou and colleagues suggested that cognitive development occurs in four cycles, with two phases in each (Demetriou et al, ; Demetriou & Spanoudis, , ). Moving across cycles is associated with the emergence of new forms of representation; changes within cycles are associated with increasing awareness of them, skill in using them, and in their alignment and interlinking.…”
Section: Development Of Cognizance Executive Control and Reasoningmentioning
confidence: 99%
“…A differentiation between mental processes is possible at 8–10 years. In this phase, awareness of different mental processes allows children to shift flexibly between them (e.g., to remember you need to observe carefully and rehearse; to sort you need to follow a sorting rule; Demetriou et al, ; Kazali, ). Children in this phase understand that more difficult items require more study time, if they are to be successfully stored and recalled (Tsalas et al, ).…”
Section: Rule‐based Thoughtmentioning
confidence: 99%
“…Specifically, intelligence is a three-level hierarchical structure involving three types of systems: (i) several broad domains of ability, such as spatial, verbal, and quantitative reasoning; (ii) domaingeneral systems of inferential and representational processes, such as fluid intelligence (Gf; basically inductive reasoning allowing processing of similarities and relations at increasing levels of abstraction) and crystallized intelligence (Gc; knowledge and skill systems crystallizing learning and experience that may be activated for understanding and problem solving; (ii) a general factor (g) mainly associated with processing efficiency, attention control, mental flexibility, and working memory (Carroll, 1993;Flynn, 2009;Jensen, 1998;Hunt, 2011). Cognizance was recently added as a major background process of g. This includes self-monitoring of mental and behavioral processes, representation and awareness of them, and systematic modification of them, including metarepresentation which generates new mental and behavioral constructs (Demetriou & Spanoudis, 2018, 2018a, 2018b.…”
Section: The Organization Of Cognition and Personality: Commonalitiesmentioning
confidence: 99%
“…New representations emerge in the first phase of each cycle and their integration dominates in the second. Transitions across cycles is driven by increasing mental self-awareness and self-regulation (Demetriou & Efklides, 2018;Demetriou et al, 2018b).…”
Section: Development Of Cognition and Personalitymentioning
confidence: 99%
“…Executive control, the ability to focus on stimuli, plan action, and flexibly change focus as needed, is a strong example. In current models of intelligence, it is a central component of Gf (Blair, 2006;Demetriou et al, 2017Demetriou et al, , 2018aDemetriou et al, , 2018b. In personality, it may be involved in two different, often orthogonal, dimensions.…”
mentioning
confidence: 99%